The Application of FT-IR Spectroscopy for Quality Control of Flours Obtained from Polish Producers - Katarzyna Sujka; Piotr Koczoń; Alicja Ceglińska; Magdalena Reder; Hanna Ciemniewska-Żytkiewicz (Journal of Analytical Methods in Chemistry)
Samples of wheat, spelt, rye, and triticale flours produced by different Polish mills were studied by both classic chemical methods and FT-IR MIR spectroscopy. An attempt was made to statistically correlate FT-IR spectral data with reference data with regard to content of various components, for example, proteins, fats, ash, and fatty acids as well as properties such as moisture, falling number, and energetic value. This correlation resulted in calibrated and validated statistical models for versatile evaluation of unknown flour samples. The calibration data set was used to construct calibration models with use of the CSR and the PLS with the leave one-out, cross-validation techniques. The calibrated models were validated with a validation data set. The results obtained confirmed that application of statistical models based on MIR spectral data is a robust, accurate, precise, rapid, inexpensive, and convenient methodology for determination of flour characteristics, as well as for detection of content of selected flour ingredients. The obtained models’ characteristics were as follows: R2=0.97, PRESS = 2.14; R2=0.96, PRESS = 0.69; R2=0.95, PRESS = 1.27; R2=0.94, PRESS = 0.76, for content of proteins, lipids, ash, and moisture level, respectively. Best results of CSR models were obtained for protein, ash, and crude fat (R2=0.86; 0.82; and 0.78, resp.).